18F-FDG PET/CT findings in a patient with blastic plasmacytoid dendritic cell neoplasm and post-transplant lymphoproliferative disorder after hematopoietic stem cell transplantation: a case report - Chen, Jinzhi; Zhang, Xi; Ma, Linlin; Gao, Yuan; Fu, Zhanli; Liu, Meng (Frontiers in Medicine, 2023)
Background Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is an extremely rare hematopoietic malignancy, which originating from precursors of plasmacytoid dendritic cells. Allogeneic hematopoietic stem cell transplantation (HSCT) is normally considered in the treatment of BPDCN patients to acquire sustained remission. Post-transplant lymphoproliferative disorder (PTLD) is a group of conditions involving abnormal lymphoid cells proliferation in the context of extrinsic immunosuppression after solid organ transplantation (SOT) or HSCT. Herein, we report a patient with BPDCN, who suffered from PTLD after allogeneic HSCT. Case presentation A 66-year-old man was diagnosed with BPDCN, confirmed by pathologic examination after splenectomy. The post-surgery 18F-fluoro-2-deoxy-D-glucose-positron emission tomography/computed tomography (18F-FDG PET/CT) showed multifocal 18F-FDG avidity in the left cheek, lymph nodes and bone marrow. The patient started chemotherapy, followed by allogeneic HSCT and immunosuppressive therapy. Four months after the HSCT, the patient developed intermittent fever and recurrent lymphadenopathy, accompanied with progressively elevated Epstein–Barr virus (EBV)-DNA both in serum and lymphocytes. 18F-FDG PET/CT was performed again and found multiple new enlarged 18F-FDG-avid lymph nodes, while the previous hypermetabolic lesions all disappeared. The pathology of mesenteric lymph node indicated a monomorphic PTLD (diffuse large B-cell lymphoma). Then the immunosuppressive medications were stopped and two cycles of Rituximab were given, and the follow-up CT scan indicated a complete response. Conclusion When patients with BPDCN recurred new enlarged lymph nodes after allogeneic HSCT and immunosuppressive therapy, PTLD should be taken into consideration. 18F-FDG PET/CT may provide additional evidence for supporting or refuting the suspicion of PTLD, and suggest lesions accessible for biopsy.